2019
DOI: 10.1128/jb.00575-18
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine Biosynthesis Regulates the Small-Colony Variant and Mucoidy in Pseudomonas aeruginosa through Sigma Factor Competition

Abstract: Mucoidy due to alginate overproduction by the Gram-negative bacteriumPseudomonas aeruginosafacilitates chronic lung infections in patients with cystic fibrosis (CF). We previously reported that disruption inde novosynthesis of pyrimidines resulted in conversion to a nonmucoid small-colony variant (SCV) in the mucoidP. aeruginosastrain (PAO581), which has a truncated anti-sigma factor, MucA25, that cannot sequester sigma factor AlgU (AlgT). Here, we showed that supplementation with the nitrogenous bases uracil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…aeruginosa is between AlgU and RpoN (a sigma factor regulating nitrogen metabolism, as well as other systems [64]), which have overlapping promoter sites upstream of the alginate biosynthetic gene algD [65]. Shifts in the concentrations of these sigma factors affect algD expression [66]. Furthermore, sigma factor competition between AlgU and the primary sigma factor RpoD has also been suggested [47].…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa is between AlgU and RpoN (a sigma factor regulating nitrogen metabolism, as well as other systems [64]), which have overlapping promoter sites upstream of the alginate biosynthetic gene algD [65]. Shifts in the concentrations of these sigma factors affect algD expression [66]. Furthermore, sigma factor competition between AlgU and the primary sigma factor RpoD has also been suggested [47].…”
Section: Discussionmentioning
confidence: 99%
“…Pyrimidine biosynthesis was also found to play a crucial role in the biofilm production phenotype (Garavaglia et al, 2012; Ahmar et al, 2019). In the present study, de novo biosynthesis of pyrimidine is supported by the identification, among others, of orotate phosphoribosyltransferase ( pyr E gene, Q8CSW7).…”
Section: Discussionmentioning
confidence: 99%
“…For experimental purposes, SCV of S. aureus (with the characteristics of clinical SCV) can be selected for in vitro by incubation in the presence of the P. aeruginosa quorum sensing molecule 4-hydroxy-2-heptylquinoline- N -oxide (HQNO) (Hoffman et al, 2006 ), although the authors are not aware whether this works with other staphylococci or other bacterial genera. It was reported that SCV of E. coli could be generated following exposure to 2-methyl-1,4-napthoquinone (Colwell, 1946 ) or copper ions (Weed and Longfellow, 1954 ) and that mutants in a number of bacterial genes can generate SCV (Santos and Hirshfield, 2016 ; Tikhomirova et al, 2018 ; Al Ahmar et al, 2019 ; Vidovic et al, 2019 ). The importance of SCV in the context of infection means that AMP activity vs. SCV could represent an important method for the treatment of chronic, recurrent and antibiotic resistant infections, but has received only limited attention in the context of AMP.…”
Section: Antimicrobial Susceptibility Testing Of Ampmentioning
confidence: 99%